Emergency laparotomy with synchronous Caesarean section for life-threatening strangulated Petersen's hernia. (November 2017) - Goh, En Lin; Goh, Yan Li; Haworth, Alexander; Shaw, Elizabeth; Wilson, Jeremy; Magee, Conor
Abstract : Introduction: Bariatric surgery is the most effective treatment for morbid obesity and its co-morbidities. Women are advised against becoming pregnant in the first 12-18 months after surgery due to the potential nutritional compromise induced by weight loss. An increasingly recognised complication following bariatric surgery are Petersen-type internal hernias. We present a case of life-threatening Petersen's hernia at 31 weeks of pregnancy in a patient who had previously undergone laparoscopic Roux-en-Y gastric bypass for morbid obesity. Case description: A 31-week pregnant 28-year-old (G2P1) presented as an emergency with abdominal pain, vomiting and absolute constipation. Two years previously she had undergone a laparoscopic Roux-en-Y gastric bypass and had lost 31kg. She was tachycardic, tachypnoeic and pyrexial. Blood tests performed showed a raised white cell count 14.4x10 9 /L, haemoglobin 114g/L, C-reactive protein 36mg/L, urea 4.1mmol/L, creatinine 64μmol/L and lactate 1.94mmol/L. An abdominal ultrasound scan showed free fluid in the abdomen and confirmed a viable intra-uterine foetus. A targeted abdominal computer tomographic (CT) scan showed a closed loop obstruction of the jejunum and proximal ileum around the Roux-en-Y reconstruction, most likely an internal hernia of Petersen. The herniated small bowel was non-enhancing, distended and fluid-filled, therefore thought to be non-viable radiologically. Results and Conclusions: The patient underwent emergency Caesarean section followed by laparotomy, small bowel resection and formation of laparotomy. She was returned to theatre 24 hours later for a second-look laparotomy. The intra-operative findings demonstrated healthy common channel measuring 270cm, bilio-pancreatic limb measuring 80cm and a long narrow gastric pouch and a small alimentary limb remnant. The gastric bypass was reversed by excising the remnant alimentary limb and fashioning gastro-gastrostomy and anastomosing the bilio-pancreatic limb to the common channel. The patient made an uneventful recovery. Clinicians involved in the management of patients with previous gastric bypass should be aware of the potential complications. We suggest that obstetric care of post-operative bariatric patients requires early liaison with the bariatric surgical team. Take home message: Obstetric care of post-operative bariatric patients requires early liaison with the bariatric team. Clinical presentations of Petersen's hernia are non-specific and clinicians should have a high index of suspicion of this diagnosis when assessing patients with previous surgery involving Roux-en-Y reconstruction.